2022
DOI: 10.1002/adma.202200839
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Lipid Nanoparticle Structure and Automated Single‐Particle Composition Analysis to Design Phospholipase‐Responsive Nanocarriers

Abstract: Lipid nanoparticles (LNPs) are versatile structures with tunable physicochemical properties that are ideally suited as a platform for vaccine delivery and RNA therapeutics. A key barrier to LNP rational design is the inability to relate composition and structure to intracellular processing and function. Here Single Particle Automated Raman Trapping Analysis (SPARTA) is combined with small‐angle X‐ray and neutron scattering (SAXS/SANS) techniques to link LNP composition with internal structure and morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“… 72 75 LNPs may be designed for stimuli-triggered release, but accuracy in physiological conditions remains a challenge. 76 79 Research and optimization are ongoing to address these limitations and enhance lipid NP performance.…”
Section: Advanced Nanotechnologiesmentioning
confidence: 99%
“… 72 75 LNPs may be designed for stimuli-triggered release, but accuracy in physiological conditions remains a challenge. 76 79 Research and optimization are ongoing to address these limitations and enhance lipid NP performance.…”
Section: Advanced Nanotechnologiesmentioning
confidence: 99%
“…The authors successfully demonstrated the advanced capabilities of SPARTA by analyzing different nanoparticle formulations, including liposomes and polymersomes, as well as the functionalization of polystyrene particles. Since its initial demonstration, SPARTA has been used to study a multitude of nanoparticle systems in recent years. Saunders et al adapted SPARTA to distinguish cargo location and loading heterogeneity within nanoparticle populations . They generated a theoretical model and showed a positive, linear correlation between the encapsulating polymer and cargo mass for membrane loading and a much lower cubic relationship for core loading.…”
Section: Imaging Drug Molecule Distribution and Delivery In Cells And...mentioning
confidence: 99%
“…Lipid nanoparticles (LNPs), as nanoparticle carriers containing mRNA, play an important role in whole-body transport [ 57 , 58 , 59 , 60 ]. Their superior biocompatibility and efficient intracellular release mechanism make them an ideal drug delivery tool [ 61 , 62 , 63 ].…”
Section: Mrna Vaccines and Tumor Immunitymentioning
confidence: 99%